2020
DOI: 10.1111/cdoe.12561
|View full text |Cite
|
Sign up to set email alerts
|

Poor parenting behaviours and dental caries experience in 6‐ To 7‐year‐old children

Abstract: Objectives The association between poor parenting and dental caries in children remains unclear. We investigated the association of poor parenting with dental caries and oral health behaviour among children aged 6‐7 years in Japan. Methods Two waves of repeated cross‐sectional surveys on children and their caregivers in Adachi City, Tokyo, were analysed. Questionnaires on parenting behaviour and the child's oral health behaviour were distributed through schools and completed by 8499 caregivers (response rate =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
23
2
1
Order By: Relevance
“…Additionally, parents play an important role in their children's oral hygiene practices. According to a cross-sectional survey performed in Japan, lack of parental supervision was considered as a risk factor for dental caries in 6-to 7-year-old children (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, parents play an important role in their children's oral hygiene practices. According to a cross-sectional survey performed in Japan, lack of parental supervision was considered as a risk factor for dental caries in 6-to 7-year-old children (32).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies it was reported that maternal education significantly influences attitudes toward children's oral health and that mothers play an important role in the development of children's dental health behavior (22,36,37). Moreover, parental practice such as feeding style and general parenting style can be relevant (32). According to a study conducted in Ohio, USA, permissive parenting style was more associated with dental caries than authoritative parenting style (38).…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Parents play a pivotal role in mitigating the risks of dental caries and promoting positive oral health behaviors in young children. [ 5 ] Parents’ oral health behaviors, including oral hygiene practices and cariogenic food consumption, are directly related to the oral health of their children. [ 6 ] This relationship needs to be considered, because ECC can negatively affect the permanent teeth, thereby leading to future dental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 265 abstracts included in the assessment, 34 were not structured, and the prevalence was higher than that previously reported by other authors [ 13 , 18 ]. Structured abstracts have been strongly recommended by the International Committee of Medical Journal Editors [ 24 ], and they are supposed to enhance the quality of the report [ 25 ].…”
Section: Discussionmentioning
confidence: 99%